Predictions and experiences regarding the implementation of the Smoke Free Initiative on a specialist NHS locked Rehabilitation Unit - E Cox , Nadia (International Journal of Psychosocial Rehabilitation, 2017)
Guidance on smoking in secondary care stated that all mental health settings should be smoke-free and provide smoking cessation support. The current study explored the concerns of staff and service users prior to the implementation of a smoke-free policy within locked rehabilitation. It aimed to capture people’s reflections on the actual experience of introducing a smoke-free environment. The study was conducted using four focus groups; with thematic analysis to analyse the data and produce themes. The findings indicated that there had been an increase in unsettled behaviour, increase in rule breaking and a ack of clarity of the rules and procedures. A complete ban would be the most constructive way to implement a smoke-free initiative, allowing service users and staff unambiguous guidelines. Least restrictive practice and client centred approaches are at the heart of mental health care; however a smoke free policy appears to contradict these philosophies within a rehabilitation setting.